INSTRUCTIONAL MATERIAL: A TOOL FOR ACHIEVEMENT IN MENSURATION AT SENIOR SECONDARY SCHOOLS IN NIGERIA - Malik, Nasrudeen Ayinde; Saddiq, Khalid (JURNAL EDUSCIENCE, 2024)
This study investigated the effects of instructional materials in secondary schools in Ogun State and how the student attitudes towards mensuration affect the student’s academic achievement. Three research questions and three null hypotheses guided the study. The quasi-experimental research design was employed to conduct the study. A sample of 65 was drawn from the population of senior secondary school students in Obafemi Owode Local Government Area of Ogun State, Nigeria. The instruments used to collect data were Mathematics achievement tests and attitude questionnaires. The pre-test was administered to both experimental and control groups and later the post-test. The researcher also administered the questionnaire to the participants. The reliability of the Likert-scale sections of the data obtained was determined by computing Cronbach’s alpha values The research questions were answered descriptively using mean and standard deviation while the hypotheses were tested inferentially at a 0.05 level of significance using Analysis of Variance (ANOVA). The result showed that students taught using instructional materials understood the concept of mensuration better than those taught with traditional/conventional methods. There was also a significant difference between the mean gain of students taught using instructional materials and those taught using traditional methods. There was no significant difference between students understanding the concept of mensuration when taught with traditional/conventional methods. It was recommended among others that mathematics teachers adopt instructional methods of teaching by using a variety and stimulating materials that instill in learners’ confidence, enthusiasm, and interest in mensuration that leads to greater achievement.